Public investment in resource-abundant developing countrie - Berg, Andrew [et al] (2013)
Develops a dynamic stochastic model to analyse the macroeconomic effects of investing resource revenues, making explicit the role of public investment inefficiency, absorptive capacity constraints, Dutch disease and financing needs to sustain capital. Demonstrates how the model can be used to determine the appropriate magnitude of the investment scaling-up and the adequate size of a stabilisation fund.